Applying the stereotype content model (SCM) and BIAS map to understand attitudinal and behavioral tendencies toward the conservation of sharks - Neves, Joao (2022)
Sharks are at increasing risk of extinction. Being a key factor in maintaining the balance of marine life in the ocean, as well as regulating the variety and abundance of the species below them in the food chain, their depletion is threatening the whole marine ecological system. Aside from the fisheries industry regulation, public opinion plays a fundamental role in any conservation effort. However, unlike other iconic sea marine animals such as dolphins, sharks receive little attention, and conservation support from the public. Many scholars attribute such neglect to sharks' bad image amongst the public. The present study was aimed at getting a better understanding of sharks' bad image, using the Stereotype Content Model/Behaviors from Intergroup Affect and Stereotypes map (SCM/BIAS map), and its association with attitudinal and behavioral tendencies toward their conservation. Participants (n = 144; Mage = 22.28; SD = 6.24; 66% female) were assessed in terms of their perceived warmth, competence, and approach-avoidance emotions related to sharks (and dolphins), as well as attitudes toward their conservation and their donation intention. Results showed that, congruent with the SCM/BIAS map, sharks fit the “threatening-awe stereotype” (high competence and low warmth), whereas dolphins align with the “protective stereotype” (high competence and high warmth). Results also showed that warmth was associated with more positive perceptions of sharks and positive attitudes toward their conservation. Warmth as a potential facilitating key factor in sharks’ conservation promotion is discussed.